Pengembangan Buku Ajar Pendamping Digital Materi Mengenali Letak Kota/Kabupaten dan Provinsi Tempat Tinggal pada Peserta Didik Kelas IV SDN Banyuajuh 3 Bangkalan - Ninik Zahrotur Rohmaniyah; Conny Dian Sumadi (Mataram University, 2026)
This research produces a product in the form of a digital companion textbook on the material of recognizing the location of the district/city and province of residence. The development model used is 4D. The objectives of this research are, (1) Developing a valid digital companion textbook based on expert validation questionnaires, (2) Developing an attractive digital companion textbook based on teacher response questionnaires and student response questionnaires, (3) Developing an effective digital companion textbook based on teacher observation sheets, student observation sheets, and student learning outcomes. The results of the study show that the digital companion textbook was declared very valid by the four experts with a percentage of 88.75%. The attractiveness of the digital companion textbook is proven by the results of the teacher response questionnaire which received a percentage of 100% and the results of the student response questionnaire of 91.5%, so it is declared very attractive. The effectiveness of the companion textbook is proven by the teacher observation sheet which received a percentage of 98.75%, student observation of 92%, student learning outcomes of 89.5% with classical completeness of 100%, so it is declared effective. Based on these results, the digital companion textbook is able to help students SDN Banyuajuh 3 understand material that was previously general in nature in the main learning source.